Adaptive Assessment Pathways for Achieving SDG 4: Strengthening Motivation and Self-Efficacy in Indonesian Nonformal Education - Afakhrul Masub Bakhtiar; Yatim Riyanto; Sujarwanto Sujarwanto (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: To examine how adaptive assessment pathways strengthen learner motivation and self-efficacy in Indonesian nonformal education, particularly in community learning centers (PKBM). It focuses on how diagnostic assessment, authentic evaluation, and personalized feedback support learners who have experienced exclusion from formal schooling. Method: A qualitative multi-site case study was conducted over ten months at two PKBM institutions in Indonesia. The study involved 57 participants, including institutional leaders, tutors, administrative staff, and learners. Data were collected through participatory observation, semi-structured interviews, and portfolio analysis. The data were analyzed thematically to identify patterns related to adaptive assessment, motivation, self-efficacy, and learner engagement. Results: The findings revealed that adaptive assessment pathways contributed to three main psychological outcomes. First, diagnostic and contextual assessment created meaningful learning experiences that enhanced intrinsic motivation. Second, portfolio-driven evaluation helped learners recognize their progress, develop self-efficacy, and build a positive learning identity. Third, personalized feedback cycles encouraged learners to monitor their own progress and develop self-regulated learning behaviors. Novelty: Offering a novel perspective by conceptualizing adaptive assessment pathways as both pedagogical and psychological mechanisms for restoring learner confidence in nonformal education. The findings highlight adaptive assessment as a transformative strategy for advancing equity, inclusion, and SDG 4 oriented learning in Indonesian PKBM contexts.